Tourism Development and Effects of Covid -19 on Tourism in Myanmar - Ni Lar Myint Htoo; Daw Win Moe Moe Kyaw (International Journal Of Tourism, 2023)
Although all tourism attractions would have a positive impact on the local population inMyanmar, COVID-19 has had a significant negative impact on the tourism industryglobally, and Myanmar is no exception. All commercial flights to Myanmar have beensuspended since April 2020, and domestic flights have also been suspended since earlySeptember. Due to the travel restrictions, this pattern abruptly stopped. Therefore, thisstudy is to evaluate the economic, social and environmental impact of Tourism industryand to highlight the impact of COVID-19 on the Tourism industry in Myanmar. Primarydata are collected from (100) stakeholders (tour operators, hoteliers, and other tourismproviders) in the tourism industry in Yangon by using simple random sampling methodthrough structured questionnaires. This study uses descriptive method to examine thecollected data. The result indicates that tourism is one of the major sources of Myanmar’sGDP. Since the combined profits from hotels, restaurants, and transportation businessesthat are partially reliant on tourism are substantially greater, at 16% of GDP, this isanticipated to have a significant influence on the economy. It has also been pointed outthat Myanmar’s tourism industry is mostly dependent on international factors and foreigntourists. Since 2021, limitations have been loosened as Myanmar has been able to controlthe COVID-19 virus. The study's findings indicate that the COVID-19 outbreak has hada detrimental economic and social impact on Myanmar's tourism sector. Financial loss, adecline in customer demand on an international and national level, disruptions in thedistribution system, and ruined connections with suppliers, customers, and employeesare just a few examples of economic repercussions. Among the business owners, thesocial impact included depression, annoyance, anxiety, and tension due to the current andpotential future circumstances. Overall analyses suggest that building the capacity ofstakeholders and encourage public-private partnership activities in order to develop andmanage future tourism sector.